2020
DOI: 10.1142/s1363919621500250
|View full text |Cite
|
Sign up to set email alerts
|

Ownership, Compensation and Board Diversity as Innovation Drivers: A Comparison of U.S. And Canadian Firms

Abstract: Using a large sample of North American firms, from 1999 to 2016, we investigate the effect of corporate governance structures, specifically ownership, board characteristics, and executive compensation contracts on innovation intensity and output. We consider both R[Formula: see text]D expenditures and patents as innovation proxies and evaluate consequences of the economic downturns of 2000 and 2008. We find that R[Formula: see text]D investment increases with ownership by institutional blockholders and with th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 72 publications
4
12
0
Order By: Relevance
“…However, a further study showed that female directors in monitoring capacity contribute better to R&D outcomes than those in an advisory capacity (Chen et al, 2021). It also argued in a North American firm's study that R&D expenditure increased when there were more female members and outside directors on the board (Atallah et al, 2021). The dominance of India as a male-dominated society (Chauhan and Dey, 2017) allows this study to replicate a similar study in India.…”
Section: Hypothesis Development 241 Female Directors and Corporate In...mentioning
confidence: 63%
See 2 more Smart Citations
“…However, a further study showed that female directors in monitoring capacity contribute better to R&D outcomes than those in an advisory capacity (Chen et al, 2021). It also argued in a North American firm's study that R&D expenditure increased when there were more female members and outside directors on the board (Atallah et al, 2021). The dominance of India as a male-dominated society (Chauhan and Dey, 2017) allows this study to replicate a similar study in India.…”
Section: Hypothesis Development 241 Female Directors and Corporate In...mentioning
confidence: 63%
“…Even though different authors have examined innovation and performance, the indicators that cause an increase in innovation have limited studies. Among the identified studies include a study that argued that R&D expenditure increased when more female members and outside directors were on the board (Atallah et al , 2021). Similarly, it is observed that female directors influence innovation performance.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Last, institutional ownership was included in the model. Although research has yet to produce conclusive evidence on whether institutional ownership hinders or facilitates innovation, its significance for innovation is undisputed (Atallah et al, 2021; Brossard et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…While R&D expenditures only capture observable innovation inputs, patenting activity reflects the successful outputs after it has invested all observable and unobservable innovation inputs. Additionally, patenting activity may be regarded as a measure of innovation efficiency (Atallah et al, 2021), and patents were closely related to development of new products that show a commercial value and were also externally validate innovation outcomes (Chen et al, 2016). Moreover, the application of patents can produce short-term profitability and can be expected to bring more persistent future benefits (Fitzgerald et al, 2021).…”
Section: Dependent Variablementioning
confidence: 99%